Awareness and practices of biomedical waste management in government health care facilities in Kamrup District, Assam - Ojah, Jutika; Sharma, Rakesh (International Journal Of Community Medicine And Public Health, 2020)
Background: Biomedical waste (BMW) is waste generated in the course of healthcare activities. It is a matter of serious concern to health and environment agencies. Objectives of the study was to assess awareness and practice of healthcare personnels regarding biomedical waste management (BMWM) in government healthcare facilities (HCF) in Kamrup district and to assess training given to healthcare workers involved in BMWM. Methods: The present study was undertaken in 109 HCF in Kamrup District, Assam. The study duration was for one year and the study population included were healthcare workers (HCW) with the help of a pretested interview schedule to elicit the knowledge of BMW management. An observatory checklist was also used to find out the practices. Results: About one-fourth of 218 respondents belonged to age group 26-30 years. Half of the respondents were nurses, 17.9% were doctors, 12.8% were pharmacists and 8.3% were waste handlers. Majority (78.4%) were aware of BMWM rules. Awareness on hazardness of healthcare waste, segregation of waste, maximum storage time of hospital waste, awareness about availability of training on healthcare waste management were found to be more among the doctors (84.6%, 79.4%, 56.4%, 82.1% respectively) and less among waste handlers (44.4%, 33.3%, 38.9%, 44.4% respectively). Only 40.8% were trained. The practice of disposing BMW in specified colour coded containers were done by 56.4% HCW. Out of 18 waste handlers, only 16.7% had the practice of wearing all the personal protective equipments (PPE) while handling BMW. All total 59.6% HCW had been vaccinated against Hepatitis B.Tetanus vaccination was taken by 77.5% HCW. Conclusions: Sensitization and training in accredited centres for HCW should be done regularly to develop awareness and motivation. Continuous monitoring and inspection of HCF need to be done.